FILSAFAT PENDIDIKAN ISLAM PERSPEKTIFONTOLOGI EPISTEMOLOGI DAN AKSIOLOGI - Muhammad Qadafi; Wedra Aprison; Ali Akbar (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
Abstract. In general, Islamic educational philosophy is an effort to guide humans in depth, both physically and spiritually, based on the Islamic religion so that the main personality is formed in accordance with Islamic teachings. Philosophy is an attitude or view of life and an applied field to help individuals evaluate their existence in a way that is more satisfying. Philosophy brings us to understanding and understanding brings us to appropriate action. Philosophy needs understanding for someone who is involved in the world of education because it determines one's thoughts and directs one's actions to achieve goals. In general, systematic philosophy has three main discussions or parts, namely; epistemology or theory of knowledge which discusses how we obtain knowledge, ontology or theory of nature which discusses the nature of everything that gives rise to knowledge, and axiology or theory of values ​​which discusses the use of knowledge.